A dynamic model of profit of residential projects in Vietnam - Nguyen, Nghia Hoai; Chinda, Thanwadee (International Journal of Strategic Property Management, 2018)
It is difficult to estimate the profit of residential projects as there are a number of complicated relationships among key profit factors. This study develops a dynamic model of the profit of residential projects in Ho Chi Minh City, Vietnam, utilizing a system dynamic approach, to examine the profit of residential projects in the long term. Five key profit factors, including the Urban Population, Buyer Capacity, Housing Supply, Housing Economics, and Housing Finance factors, are used to develop the dynamic model. Simulation results reveal that the average profit of residential projects in Ho Chi Minh City, Vietnam, in the next 20 years, is 35%, with a minimum and maximum profit of 19% and 41%, respectively. Scenario analyses recommend that a 30% down payment, a 25-year payment period, and a debt to equity ratio of 40% are the best strategies that residential companies should use to maximize profit in the long term. It is also recommended that debt to equity ratio and house price should be maintained in the early years to assist low-income households. The developed model can be used as a starting point to develop a software that allows developers to examine strategies by simply inputting their available data.